Music to move: effects of listening to preferential music on aerobic endurance performance and rate perceived of exertion responses / Maisarah Mohd Saleh ... [et al.] - Mohd Saleh, Maisarah; Abd Razak, Fatin Aqilah; Abd Rahman, Siti Aishah; Ab Razak, Rozella; Sanuddin, Nurul Diyana; Linoby, Adam; Mohamed Kassim, Nur Atikah; Wiz, Ahmad Waqi (Universiti Teknologi MARA, 2023)
Music has been shown to reduce the rating of perceived exertion (RPE), increase motivation and enhance exercise performance. However, the effects of exercise performance and RPE with recommended tempo songs are less conclusive. The purpose of this study was to examine the effects of listening to preferred music on aerobic endurance performance and rate perceived of exertion responses. Thirty physically active males (mean ± SD: 18.27 ± 0.45 years, body mass 21.45 ± 1.40 kg·m-2) were recruited for this study. In the experimental study design, participants completed two trials separated by a minimum of 72 hours. In music condition, participants listened to their own preferred music (selection song tempo range was between 121 - 131 bpm). Participants were required to complete a 2.4 km maximal effort run with RPE measured throughout the test. Time to complete 2.4 km aerobic endurance performance and RPE score were significantly lower (PRE: in music condition (11.30 min ± 1.67; 4.83 ± 1.15) compared with in no music condition (11.58 min ± 1.59; 5.43 ± 0.73). In conclusion, the findings of this study indicated that listening to music preference has a significant effect on running performance during 2.4 km aerobic endurance performance. The results from this study could hold important implications for the application of music and enduring aerobic endurance exercise.